Recurrent Haemophilus Influenzae Mediastinitis. Success of a Treatment Combining Redon Drains and Vacuum-Assisted Closure: Recurrent Haemophilus influenzae mediastinitis - ATMANI, Noureddine; SEGHROUCHNI, Aniss; MOUTAKIALLAH, Younes; ELBEKKALI, Youssef (RA Journal of Applied Research, 2021)
Mediastinitis is a dreadful complication after cardiac surgery, in severe forms mortality can reach 50%. The results of the surgery depend on the early management and the surgical technique. Treatment by vacuum-assisted closure -VAC therapy- has shown favorable results. We report the case of a 69-year-old man with diabetes who underwent triple coronary bypass grafting surgery under extracorporeal circulation. He presented a postoperative mediastinitis treated by closed continuous mediastinal irrigation. The evolution was marked by a recurrence of mediastinitis with a severe form. The patient underwent a surgical revision with placement of closed-drainage aspiration with Redon catheters and vacuum-assisted closure therapy with a good result. The evolution was favorable at the one and three month controls. Our observation demonstrates the benefit of the association of Redon drains aspiration and VAC therapy in the management of severe mediastinitis after cardiac surgery.